O ensino de filosofia como práxis educativa na formação da autonomia dos discentes - SANTOS, Débora Cristine Fernandes Oliveira dos (2021)
The general objective of this study is to investigate the teaching of Philosophy, as a proposal for an educational praxis committed to exercising the autonomy of students at the Professor Ezelberto Martins Teaching Center, a school located in the Vila Sarney industrial district, a rural area of the municipality of São Luís do Maranhão. . The work has specific objectives: to identify the concepts of dialogicity and its relevance in the teaching of Philosophy as a path to autonomy; recognize the theoretical- methodological concepts used in Philosophy classes; observe the educational practice in the philosophy classes of the 2nd and 3rd year classes. Based on the theoretical assumptions of Paulo Freire (2002) and Jean Paul Sartre (2015), the research discusses the categories autonomy, freedom and praxis, expanding their relationship to the teaching of Philosophy. It is epistemologically based on phenomenology and fits into its methodological approach as qualitative research, in addition to using the technical procedures of bibliographic, documentary, field and intervention research. The text presented is divided into five sections, in which the theme is presented in the first, bringing its relevance to the proposed study; in the second, it is concerned with dealing with the concepts of dialogicity and its importance for the teaching of Philosophy; in the third section, the educational concept of Freire and Sartre is discussed, bringing the categories of autonomy, freedom and praxis; the fourth section analyzes the research locus and the subjects' speeches, where the research results are brought; and the fifth section ends with the final considerations regarding the work developed.